Determinants on Teachers’ Performance With Job Satisfaction As A Mediation - Munajiyah, Siti; Joko Raharjo, Tri; Murwatiningsih, Murwatiningsih (Educational Management, 2020)
Teachers’ performance is an urgent matter to achieve the quality of Indonesian education. All of schools have target to get optimal teachers’ performance. Thus, it is important as a teacher to know the determinants on teachers’ performance. Some of the determinants on teachers’ performance in the study are principal’s leadership, cultural organization, competence, and job satisfaction. The study aims to analyze the influences of principals’ leadership, competence, and organizational culture on teachers’ performance through job satisfaction in private junior high school especially Southern Brebes. The population of the study was 108 teachers (S.1 degree) of four schools and 78 teachers as a sample which was taken by Slovin formula where e = 6% (0.06) and the sampling technique used proportional random sampling. Furthermore, data collection used questionnaire and data analysis technique used a path analysis for hypotheses test with SPSS (statistical packages of social scientists) for Windows version 23.0 application computer program with level of significance at 0.05. The results of the study found that principals’ leadership, cultural organization and competence have positive and significant influences on teachers’ performance with job satisfaction as mediation. It means that rising of principals’ leadership, organizational culture and competence will influence on job satisfaction, thus teachers’ performance will increase too. Therefore, the suggestion for teachers that they should able to increase teachers’ performance. It is an effort to improve the progress of Indonesian education.